Pengaruh Akuntansi Lingkungan dan Audit Lingkungan Terhadap Sosial Ekonomi Masyarakat dengan Good Corporate Governance Sebagai Pemoderasi: Akuntansi - Hasanah, Zahrotul; Sembiring, Carolyn Lukita; Astriani, Devi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The issue of environmental pollution is often a hot topic in discussions. Companies are asked to take part in conservation through special financing related to the environment and compliance with environmental management to safeguard stakeholder interests and maintain good relations with the surrounding community. This research aims to determine the influence of Environmental Accounting, Environmental Audit implemented by companies on the Social Economy of the Community with the principles of Good Corporate Governance as a moderator. The data source used is primary data through tabulated questionnaires distributed to several companies in Karawang Regency via the LinkedIn social media application. The random sampling technique produced a sample of 66 respondents among employees who work at companies in Karawang Regency. Testing uses Partial Least Square (PLS SEM) analysis using Smartpls version 4.0. The results of the research show that Environmental Accounting has no effect on Community Social Economy, but Environmental Audit has a positive influence on Community Social Economy. Good Corporate Governance has a direct influence on the social economy of society, but cannot moderate the influence of Environmental Accounting and Environmental Audit on the social economy of society.